Piloting White Spaces for DSpaces in Malawi - Mikeka, Chomora (My University, 2013)
In this paper, the author describes a potential application that exploits the White Spaces identified in the UHF television band in Malawi to be the channel to connect to University digital repositories based on the DSpace architecture. The Malawi TV White Spaces (TVWS) network was deployed from the 11th September, 2013 in Zomba district (University town), with three stations as pilot in key economic sectors namely; education, security and seismic monitoring and mitigation. St. Mary’s Girls Secondary School is one of the pilot stations in the education sector. The ICT-teacher at the school was trained and certified ready to support and sustain the TVWS deployment and the applications running on the TVWS infrastructure. This paper reports on the access that the TVWS network is providing to the senior level students (Form III and Form IV) from the School’s Computer Lab to the University of Malawi’s DSpace at Chancellor College Campus Library. A parametric study of the link performance between St. Mary’s and Chancellor College show data rates up to 700kbps in terms of downstream application data throughput and a per second packet rate of 60, provided that the TVWS base station (BS) is wireless backhauled to a dedicated 2Mbps internet bandwidth stream and that the TVWS link at UHF channel 31 (554 MHz) from the BS to St. Mary’s client premise equipment (CPE) measures a Signal-to-Noise Ratio (SNR) of 25.98 dB.
Keywords: White Spaces; DSpace; ICT; Spectral Sensing; SOCIAL SCIENCES::Statistics, computer and systems science::Informatics, computer and systems science::Databases